Decentralising basic education in Indonesia: Lessons learned and the road ahead - Rudi Hartono; Indria Nurfadanti; Hendri Hendri (Institute of Information Technology and Social Science (IITSS), 2024)
This paper examines the implementation and outcomes of educational decentralization in Indonesia's basic education sector, analyzing the transfer of authority from central government to regional and local levels following the 1999 decentralization reforms. Through a comprehensive review of policy frameworks, implementation challenges, and empirical evidence from various districts, the study evaluates how decentralization has affected educational access, quality, and equity across Indonesia's diverse regions. The analysis reveals mixed results: while decentralization has improved local responsiveness and community participation in some areas, significant disparities persist between well-resourced urban districts and under-resourced rural regions. Key challenges identified include uneven fiscal capacity among local governments, inconsistent implementation of national standards, and varying levels of administrative capability at district levels. The paper highlights successful practices from high-performing districts, including innovative school-based management models, effective community engagement strategies, and efficient resource allocation mechanisms. Drawing from these lessons, the study proposes policy recommendations for strengthening the decentralized education system, including enhanced capacity-building programs for local education offices, improved inter-governmental coordination mechanisms, and more equitable resource distribution formulas. The findings suggest that while decentralization holds promise for contextualizing education to local needs, sustained national support and strategic oversight remain essential to ensure quality and equity. This analysis contributes to ongoing debates about balancing local autonomy with national standards in developing countries' education systems and offers insights for refining Indonesia's decentralized education governance moving forward.